Anatomy of Endovascular Arteriovenous Fistula Creation - Cornman-Homonoff, Joshua; Razdan, Rishi; Lozada, Juan Carlos Perez (Seminars in Interventional Radiology, 2025)
Endovascular creation of arteriovenous fistulas for hemodialysis access represents a promising alternative to surgical dialysis access provision. However, because the two available devices rely on the adequacy of the native vascular configuration, not all patients are candidates. Thus, a precise grasp of upper extremity vascular anatomy and the ability to apply that knowledge clinically are required. The purpose of this article is to provide an overview of endovascular arteriovenous creation, focusing on anatomic considerations, procedural steps, and outcomes.
Keywords: dialysis; fistula; endoAVF; anatomy; interventional radiology